Wild Strawberry Fragaria vesca L. extracts Hepatoprotective Activities Against Paracetamol-Induced Hepatotoxicity in Male Wistar Rats - Sihning E. J. T; Diah Purwaningsari; Nita Pranitasari; Liliawanti (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Administration of high-dose paracetamol had been indicated to induce several molecular and biochemical cascades of hepatotoxicity. The abundant amount of ROS formation following the uptake of the medication exceeds the physiologic antioxidant capacity of the body, leading to the occurrence of oxidative stress. Wild strawberries (Fragaria vesca L)extractsare thought to have hepatoprotective activities regarding the high activity of antioxidants contained.Method: Aspartate Transaminase (AST) activity was used as a marker of hepatotoxicity. In the 10 days trial, randomized samples of 24 male Wistar rats (Rattus Norvegicus) were used and divided into three groups: 1 group without treatment, 1 group receiving oral paracetamol 1750 mg/kg in CMC-Na suspension, and 1 group receiving oral paracetamol 1750 mg/kg following administration of strawberry extract 400 mg/kg. The strawberry extract was administered from day 1 to 10, while high-dose paracetamol was administered on day 9. AST activity analysis was done on day 10 of the trial. Significant results were found showing an increased AST activity in the paracetamol-only group (p=0.001) and a decreased AST activity in the group receiving strawberry extract (p=0.001). Conclusion: Fragaria vesca L extracts were proven in vivo to have hepatoprotective activities against paracetamol-induced hepatotoxicity